Comparison of the bilateral and unilateral barbell hip thrust - Palmer, J. L.; Needham, L.; Brazil, A.; Bezodis, I. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to quantify the kinetics and kinematics of the unilateral (UL) barbell hip thrust and compare UL biomechanics with the bilateral (BL) barbell hip thrust. Ten resistance trained males performed three sets of three repetitions UL and BL at 10 repetition maximum intensity. The biomechanics of each lift were analysed using 3D motion capture and force plates that were floor mounted and instrumented in to a bespoke rig. Joint kinetics and kinematics were calculated in the sagittal, frontal and transverse planes. It was concluded that UL loaded the hip joint to a greater extent than the BL across all three planes. The current study offers novel insight to the biomechanical demand of the unilateral hip thrust and has implications for exercise selection within the physical preparation of athletes.